Companies and the Sustainability Due Diligence Directive and their impact on creative cities: A regulatory contribution - Paredes Serrano, Cristina; Gismera Tierno, Eduardo (Street Art & Urban Creativity, 2025)
The phenomenon of cities adapting to become healthier and more habitable spaces has forced the companies that are part of them to become sustainable places and prepared so that their workers can contribute to being part of a better city. Using a qualitative methodology based on documentary analysis, this research paper analyses the existing regulations on sustainability and tries to assess the degree of commitment of current companies to become an active part of prosperous creative cities.